Contraceptive Choice and Use of Dual Protection Among Women Living with HIV in Canada: Priorities for Integrated Care. Issue 4 (29th November 2017) - Kaida, Angela; Patterson, Sophie; Carter, Allison; Loutfy, Mona; Ding, Erin; Sereda, Paul; Webster, Kath; Pick, Neora; Kestler, Mary; de Pokomandy, Alexandra
Abstract: CONTEXT: Preventing unintended pregnancy and HIV transmission is important for women with HIV, but little is known about their contraceptive use, particularly under current antiretroviral therapy (ART) recommendations for treatment and prevention. METHODS: The prevalence of contraceptive use and of dual protection was examined among 453 sexually active women with HIV aged 16–49 and enrolled in the Canadian HIV Women's Sexual and Reproductive Health Cohort Study in 2013–2015; multivariable logistic regression was used to identify correlates of use. Two definitions of dual protection were assessed: the World Health Organization (WHO) definition (consistent condom use alongside another effective method) and an expanded definition (consistent condom use or a suppressed HIV viral load alongside an effective method). RESULTS: Overall, 73% of women used effective contraceptives, primarily male condoms (45%) or tubal ligation (19%). Eighteen percent practiced WHO‐defined dual protection, and 40% practiced dual protection according to the expanded definition. Characteristics positively associated with contraceptive use were younger age, having been pregnant, being heterosexual, being unaware of ART's HIV prevention benefits and having had partners of unknown HIV status (odds ratios, 1.1–6.7). Younger age and perceived inability to become pregnant were positively associated with both definitions of dual protection (1.04–3.3); additionally, WHO‐defined dual protection was associated with perceiving HIV care to be women‐centered and having had partners of unknown HIV status (2.0–4.1), and dual protection under the expanded definition was related to having been pregnant (2.7). CONCLUSIONS: Future research should explore how sustained ART and broader contraceptive options can support women's sexual and reproductive health care needs.